Patients' evaluation of a post-myocardial infarction teaching programme administered by nurses. Issue 700 (February 1984) - Jenkins, B.; Mayberry, J. F.; Kent, S.; Colbourne, G.
Abstract : Two-hundred and twenty-eight patients admitted to a District General Hospital Coronary Care Unit with a confirmed myocardial infarction were given a detailed information session by nurses. Information included a detailed programme of exercise during convalescence and attitudes toward diet, smoking and sexual intercourse. Patients were asked to assess the value of these sessions using questionnaires administered during convalescence. Between 76% and 91% of patients considered the presentation necessary and there was a significant improvement in their understanding of what an infarction was. More than 80% of patients found a booklet entitled Recovering from your Heart Attack particularly helpful. The great majority of patients believed that more health education should be given at school and that members of the general public should be taught the techniques of cardio-pulmonary resuscitation. The teaching programme appears to have reduced the admitted smoking habits of patients. On admission 56% of patients were smokers. This fell to 7% at the end of 3 weeks, but had risen to 17% at 6 months.